2018
DOI: 10.1523/jneurosci.0703-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Movement Intervention Enhances Extinction via Amygdala Deactivation

Abstract: Improving extinction learning is essential to optimize psychotherapy for persistent fear-related disorders. In two independent studies (both = 24), we found that goal-directed eye movements activate a dorsal frontoparietal network and transiently deactivate the amygdala (η = 0.17). Connectivity analyses revealed that this downregulation potentially engages a ventromedial prefrontal pathway known to be involved in cognitive regulation of emotion. Critically, when eye movements followed memory reactivation durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 61 publications
(51 reference statements)
2
85
0
Order By: Relevance
“…However, the fact that participants needed to hold their answer for a couple of seconds might have comprised some cognitive demand during image presentation. It has been recently reported that working memory load during extinction can suppressed amygdala activity and subsequently reduce recovery of threat responses (Voogd, Neville, Roelofs, Fernández, & Hermans, 2018). However, the cognitive demand in this task (i.e., 27 s of a 2N-Back task and goal-directed eye-movements) further exceeds the one required for our detention task.…”
Section: Discussionmentioning
confidence: 91%
“…However, the fact that participants needed to hold their answer for a couple of seconds might have comprised some cognitive demand during image presentation. It has been recently reported that working memory load during extinction can suppressed amygdala activity and subsequently reduce recovery of threat responses (Voogd, Neville, Roelofs, Fernández, & Hermans, 2018). However, the cognitive demand in this task (i.e., 27 s of a 2N-Back task and goal-directed eye-movements) further exceeds the one required for our detention task.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, amygdala inhibition is also found when participants perform a working memory task (Cousijn et al, 2010;de Voogd et al, 2018b;Qin et al, 2009) or play a computer game of Tetris (Price et al, 2013). Furthermore, greater decreases in BOLD-signal in the amygdala are observed when the cognitive load increases (de Voogd et al, 2018a).…”
Section: Introductionmentioning
confidence: 94%
“…One way extinction learning may be improved is through an eye movement intervention (de Voogd et al, 2018b). This idea is based on the notion that goal-directed eye movements form an important part of eye movement desensitization and reprocessing (EMDR).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations